Οι Τέσσερεις Καβαλάρηδες - (:unkn) unknown (My University, 2021)
Η συντέλεια του κόσμου υπό το φως της Αλγοριθμικής Τέχνης. Οι τέσσερεις Καβαλάρηδες της Αποκάλυψης του Ιωάννη μέσα από βασικά στοιχεία μαθηματικών, απλοϊκά σχήματα, και την πεπερασμένη φύση των αλγορίθμων.

The fire-and-brimstone in the light of Algorithmic art. The four Horsemen of the Apocalypse of John through basic elements of mathematics, simplistic shapes, and the finite nature of algorithms.
The Four Horsemen
Keywords: Έργο Τέχνης, Αλγοριθμική Τέχνη, Αποκάλυψη του Ιωάννη; Artwork, Algorithmic Art, Apocalypse of John